(untitled) (Indian Journal of Public Health Research & Development, 2020)
Research awareness and involvement in yoga for health-related results are growing worldwide. Patanjali Yoga relieves stress and fatigue which haves turned into one of the few major challenges confronting the medical fraternity in present times. Yoga let go the body from any type of muscular or chronic strain and rejuvenates the body from exhaustion, body aches, stress, aids to ease the body and mind, enhances concentration and alertness, and frees the soul. It helps one to create integrity amongst his outward self as well as his innermost self. If the practices are followed meticulously then Patanjali Yoga develops a constructive effect both in the inward and outer selves of an organism. Patanjali’s yoga practice aims to bind the individual self with the Ultimate One and one can achieve this union by regulating and discarding the ever- arising ‘vrittis’ or amendments of the mind. With Patanjali Yoga mind can be balanced through the exact kind of discipline and training. The purpose of this paper was to study the effect of Patanjali Yoga practice on mental health and moral judgment of experimental group of juvenile delinquents. Pre and post experimental design was used in this research work. Patanjali Yoga practices were used as independent variables whereas mental health and moral judgments of delinquents as dependent variables. A sample of 70 delinquents of age group (13-18 years) from Government Observation Home in Agra district was chosen with random selection method. There were two groups –experimental group (n=35) and control group (n=35). Patanjali Yoga practices were imparted to delinquents for 90 days with duration of one hour each day. For measuring the moral judgment of delinquents, moral judgment test by Juri Baruh (2004) and for measuring mental health, mental health battery by A.K. Singh and Alpana SenGupta (2008) were used. Mean, Standard deviation and t-test were carried out for data analysis. The findings suggest that mental health factors like emotional stability, adjustment, autonomy, security-insecurity and self-concept were found to be of average level and intelligence ranged from average to low in experimental and control group delinquents. It was also found that Patanjali Yoga plays a significant role by strengthening emotional stability, adjustment and self -concept in delinquents, however, the Patanjali yoga does not significantly affects mental health factors like autonomy, security-insecurity and intelligence in delinquents. The findings also concluded that Patanjali Yoga does not affect moral judgments of delinquents.